Three Interesting Sequences - Dr. R. Sivaraman (International Journal of Advanced Science and Technology, 2020)
In mathematics, sequences play an important role in understanding of patterns and structures of mathematical objects. Among several amusing mathematical sequences, I discuss about three sequences in this paper. The subtle connections arising between them have been discussed in detail in this paper. Finally, the limiting behaviors of all these three sequences are found to be equal, proving asymptotically they behave in same way